2018
DOI: 10.1016/j.diabres.2018.02.023
|View full text |Cite
|
Sign up to set email alerts
|

IDF Diabetes Atlas: Global estimates of diabetes prevalence for 2017 and projections for 2045

Abstract: The new estimates of diabetes prevalence, deaths attributable to diabetes and healthcare expenditure due to diabetes present a large social, financial and health system burden across the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
3,849
7
144

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 5,658 publications
(4,367 citation statements)
references
References 20 publications
32
3,849
7
144
Order By: Relevance
“…Diabetes mellitus (DM) is a global health problem. It was estimated that in 2017, 425 million people were living with diabetes and by 2045, 629 million will become diabetic . In 2015, the direct and indirect global costs of DM were almost 2% of global gross domestic product, which equates to nearly 1.5 trillion American dollars .…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a global health problem. It was estimated that in 2017, 425 million people were living with diabetes and by 2045, 629 million will become diabetic . In 2015, the direct and indirect global costs of DM were almost 2% of global gross domestic product, which equates to nearly 1.5 trillion American dollars .…”
Section: Introductionmentioning
confidence: 99%
“…According to the data obtained from the International Diabetes Federation and related studies, more than 400 million people (age 18-99 years) are diagnosed with diabetes worldwide, and more than 90% of them suffer from type 2 diabetes (T2D) (Cho et al, 2018;Zheng et al, 2018). Diabetes is characterized by hyperglycemia, polyuria, polydipsia, and polyphagia, and could be divided into type 1 and type 2, according to different pathogeneses.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Clinical epidemiologists have revealed that T2DM is chiefly rising in the developing countries. Instead, they have rose from over 2 million in 2004 to nearly 3.5 million in 2015 and have become a critical public health challenge.…”
Section: Introductionmentioning
confidence: 99%